Respuestas

2012-08-18T00:57:02+02:00

te queda asi:

(1-cos a). (1+ 1/cos a).(cos a)/(sen a)=

(1+ 1/cos a - cos a -1). cos a/sen a=

(1-cos al cuadrado de a/cos a). cos a/sen a=

sen al cuadrado de a/ cos a. cos a /sen a=

sen a.cos a/cos a=

sen a

de un miembro llegamos al otro para resolverlo..

2012-08-18T00:59:10+02:00

(1-cos(a))*(1+(1/cos(a))*(cos(a)/sen(a))      *sec(a)= 1/cos(a)

(1-cos(a))*((1+cos(a))/cos(a))*(cos(a)/sen(a))

 

(sen^2(a)*cos(a))/(cos(a)*sen(a))             *(1-cos(a))*(1+cos(a))= 1-cos^2(a)= sen^2(a) simplifica  y te queda sen (a) sen (a) =sen (a)